Carotid body denervation improves autonomic and cardiac function and attenuates disordered breathing in congestive heart failure. (14th January 2014) - Marcus, Noah J.; Del Rio, Rodrigo; Schultz, Evan P.; Xia, Xiao‐Hong; Schultz, Harold D.
Abstract : Key points: A strong correlation between disordered breathing patterns, elevated sympathetic nerve activity and enhanced chemoreflex sensitivity exists in patients with heart failure. Evidence indicates that disordered breathing patterns and increased sympathetic nerve activity increases arrhythmia incidence in patients with heart failure. Enhanced coupling between sympathetic and respiratory neural drive underlies elevated sympathetic nerve activity in an animal model of sleep apnoea. We investigated the impact of carotid body chemoreceptor denervation on sympathetic nerve activity, disordered breathing and sympatho‐respiratory coupling in an animal model of heart failure. Renal sympathetic nerve activity, apnoea/hypopnoea incidence, variability measures of tidal volume and respiratory rate and arrhythmia incidence were quantified during resting breathing in heart failure animals with and without carotid body ablation. Our results indicate that carotid body chemoreceptor denervation reduces sympathetic nerve activity, disordered breathing patterns, arrhythmia incidence and sympatho‐respiratory coupling in experimental heart failure. These findings suggest that device‐oriented ablation of carotid body chemoreceptors is a viable treatment option for reduction of sympathetic nerve activity, disordered breathing patterns and arrhythmia incidence in heart failure. Abstract: In congestive heart failure (CHF), carotid body (CB) chemoreceptor activity is enhanced and is associated with oscillatory (Cheyne–Stokes) breathing patterns, increased sympathetic nerve activity (SNA) and increased arrhythmia incidence. We hypothesized that denervation of the CB (CBD) chemoreceptors would reduce SNA, reduce apnoea and arrhythmia incidence and improve ventricular function in pacing‐induced CHF rabbits. Resting breathing, renal SNA (RSNA) and arrhythmia incidence were measured in three groups of animals: (1) sham CHF/sham–CBD (sham–sham); (2) CHF/sham–CBD (CHF–sham); and (3) CHF/CBD (CHF–CBD). Chemoreflex sensitivity was measured as the RSNA and minute ventilatory ( V ̇ E ) responses to hypoxia and hypercapnia. Respiratory pattern was measured by plethysmography and quantified by an apnoea–hypopnoea index, respiratory rate variability index and the coefficient of variation of tidal volume. Sympatho‐respiratory coupling (SRC) was assessed using power spectral analysis and the magnitude of the peak coherence function between tidal volume and RSNA frequency spectra. Arrhythmia incidence and low frequency/high frequency ratio of heart rate variability were assessed using ECG and blood pressure waveforms, respectively. RSNA and V ̇ E responses to hypoxia were augmented in CHF–sham and abolished in CHF–CBD animals. Resting RSNA was greater in CHF–sham compared to sham–sham animals (43 ± 5% max vs . 23 ± 2% max, P  < 0.05), and this increase was not found in CHF–CBD animals (25 ± 1% max, P  < 0.05 vs . CHF–sham). Low frequency/high frequency heart rate variability ratio was similarly increased in CHF and reduced by CBD ( P  < 0.05). Respiratory rate variability index, coefficient of variation of tidal volume and apnoea–hypopnoea index were increased in CHF–sham animals and reduced in CHF–CBD animals ( P  < 0.05). SRC (peak coherence) was increased in CHF–sham animals (sham–sham 0.49 ± 0.05; CHF–sham 0.79 ± 0.06), and was attenuated in CHF–CBD animals (0.59 ± 0.05) ( P  < 0.05 for all comparisons). Arrhythmia incidence was increased in CHF–sham and reduced in CHF–CBD animals (213 ± 58 events h –1 CHF, 108 ± 48 events h –1 CHF–CBD, P  < 0.05). Furthermore, ventricular systolic (3.8 ± 0.7 vs . 6.3 ± 0.5 ml, P  < 0.05) and diastolic (6.3 ± 1.0 vs . 9.1 ± 0.5 ml, P  < 0.05) volumes were reduced, and ejection fraction preserved (41 ± 5% vs . 54 ± 2% reduction from pre‐pace, P  < 0.05) in CHF–CBD compared to CHF–sham rabbits. Similar patterns of changes were observed longitudinally within the CHF–CBD group before and after CBD. In conclusion, CBD is effective in reducing RSNA, SRC and arrhythmia incidence, while improving breathing stability and cardiac function in pacing‐induced CHF rabbits.